Synchronous carotid endarterectomy and off-pump coronary bypass: an updated, systematic review of early outcomes. - Fareed, K; Rothwell, P; Mehta, Z; Naylor, A (2009)
OBJECTIVES: To update our previous systematic review of outcomes following synchronous carotid endarterectomy (CEA) and off-pump coronary artery bypass grafting (OFF-CABG). DESIGN: A systematic review of operative risks reported in published studies of synchronous CEA plus OFF-CABG procedures. RESULTS: We identified 12 eligible studies, including data on 324 synchronous CEA plus OFF-CABG procedures. Operative mortality was 1.5% (95% confidence interval (CI): 0.3-2.8), the risk of death or ipsilateral stroke was 1.6% (0.4-2.8%), risk of death or any stroke was 2.2% (95% CI: 0.7-3.7) and the risk of death, stroke or myocardial infarction was 3.6% (95% CI: 1.6-5.5). CONCLUSIONS: Limited published data on 324 patients suggest that early outcomes after synchronous CEA plus OFFCABG are better than those following staged or synchronous CEA plus CABG where the cardiac procedure was performed on-pump. This may, however, be attributed to publication bias, case selection or the fact that the aorta was not manipulated or cannulated, rather than CEA being primarily responsible for the lower stroke risk. Colleagues with unpublished experience of CEA plus OFF-CABG are encouraged to submit their data to further inform the debate.